Feasibility Analysis of Sorgum Farming in Patihan Village, Babat District, Lamongan District, East Java Province - Mahiro, Septiana Dina; Hidayat, Syarif Imam; Laily, Dona Wahyuning (Universitas Udayana, 2023)
Indonesia's current food position still depends on rice. This is related to the level of food security. To support food security, this can be done by promoting the cultivation of sorghum. Sorghum can be a rice substitute product. Sorghum has long been cultivated in Indonesia, and there are several areas where it is planted, namely Patihan Village, Tripe District, Lamongan Regency. In 2016-2017, there was an increase in sorghum productivity in Patihan Village by 7 tonnes/ha. But in 2018-2020 there was a decrease in sorghum productivity which reached 0 tons/ha. The decline in sorghum productivity can affect farmers' income. The decline in the level of productivity of sorghum is inseparable from the existence of problems. The purpose of this research is to analyze the feasibility of sorghum farming in Patihan Village, Tripe District, Lamongan Regency, and to analyze the problems in sorghum farming. The analytical method used is the R/C Ratio and qualitative descriptive. The results showed that the R/C Ratio value was 0.26, meaning that sorghum farming in Patihan Village, Babat District, Lamongan Regency in 2021 is not feasible. The problem faced by sorghum farmers in sorghum farming is the existence of rat pests that cannot be controlled, resulting in crop failure and losses